2010
DOI: 10.1186/1744-9081-6-76
|View full text |Cite
|
Sign up to set email alerts
|

Plasma neuropeptide Y: a biomarker for symptom severity in chronic fatigue syndrome

Abstract: BackgroundChronic fatigue syndrome (CFS) is a complex, multi-symptom illness with a multisystem pathogenesis involving alterations in the nervous, endocrine and immune systems.Abnormalities in stress responses have been identified as potential triggers or mediators of CFS symptoms. This study focused on the stress mediator neuropeptide Y (NPY). We hypothesized that NPY would be a useful biomarker for CFS.MethodsThe CFS patients (n = 93) were from the Chronic Fatigue and Related Disorders Clinic at the Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
54
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 67 publications
(74 reference statements)
1
54
0
Order By: Relevance
“…The physiological concentration of plasma NPY is approximately 5×10 -11 M ~1.5×10 -10 M [26]. Our experiments demonstrated that at these physiologically relevant concentrations NPY had no significant role or just a weak role on preadipocyte proliferation in vitro.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The physiological concentration of plasma NPY is approximately 5×10 -11 M ~1.5×10 -10 M [26]. Our experiments demonstrated that at these physiologically relevant concentrations NPY had no significant role or just a weak role on preadipocyte proliferation in vitro.…”
Section: Discussionmentioning
confidence: 75%
“…Thus, both the central NPY and peripheral NPY especially fat-derived NPY may affect the growth of adipose tissue. Although the serum NPY levels were higher in obese subjects [28], the concentration is remain ranging approximately 1×10 -10 M ~3.4×10 -10 M [26,28], which should have no effect on preadipocytes proliferation based on our data. Nonetheless, the exact level of NPY which produced in adipose tissue remain unclear, we infer that if the adipose tissue could produce supraphysiolagical NPY (even nearly approach 10 -7 M), the growth of adipose tissue may be influenced by high dose of NPY.…”
Section: Discussionmentioning
confidence: 90%
“…First, adolescent CFS is associated with enhanced sympathetic nervous activity, low-grade systemic inflammation, attenuated hypothalamus-pituitary-adrenal axis function, slight cognitive impairment, and large activity reduction, but not with common is consistent with a report of high plasma neuropeptide Y levels. 41 Sympathetic enhancement might result from physical deconditioning. In the present study, however, neither plasma norepinephrine level nor heart rate responsiveness was associated with the number of steps per day in patients with CFS (Supplement [eTable 12]).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we used three concentrations of NPY (10 -7 , 10 -9 and 10 -11 M) to induce hADSCs differentiation. The physiological concentration of NPY in human body is 10-10~10-11 M [22,23]. Before formal experiments, the lower doses of NPY at 10-13 M and 10-15 M which regulated differentiation had been checked and we found that the lower doses had no effects on differentiation.…”
Section: Discussionmentioning
confidence: 99%